Hedonic Value Dan Eudaimonic Value Pada Quality Of Life Dan Purchase Behavior Produk Starbucks - Firmansyah, Ade; Burhanudin, Burhanudin (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
The globalization has an impact on socia life so that lifestyle changes occur. The entry of foreign products and hedonic behavior to obtain a quality of life is a form of influence of globalization. Quality of life has an important role in the current consumer phenomenon. This study aims to determine the effect of hedonic value and eudaimonic value on the quality of life, which in turn will affect consumer behavior. This research is included in quantitative research with data collection techniques using questionnaires in google form. The results in this study indicate that hedonic value and eudaimonic value have a significant influence on the quality of life of consumers, which in turn has a significant influence on purchasing behavior. The results of this study indicate that someone buys Starbucks products with hedonic value and eudaimonic value needs to achieve quality of life, which in turn can affect their buying behavior.